Impact assessment of zero-tillage on soil microbial properties in rice-wheat cropping system - CHAUDHARY, ANITA; SHARMA, D K (The Indian Journal of Agricultural Sciences, 2019)
Soil health which is deteriorating at the fast pace due to excessive use of fertilizers can be restored by the adoption of resource conservation technologies (RCT) which can affect the soil properties. The soil health can be measured by the ability of the microorganisms which can serve as early warning signals. In a farmers’ participatory field located in Karnal, Haryana, India, soil was sampled spatially and temporally at different stages of the wheat crop. The fields measuring one acre were under conventional tillage (CT), zero tillage (ZT) for the last five years under rice wheat cropping system. As the crop season of wheat progressed, standing stubble from the previous rice crop decomposed, resulting in higher microbial biomass carbon (MB-C) in zero tillage treatment than the conventional tillage. MB-C ranged from 70–269 μg C/g soil as compared to 62–200 μg C/g of soil. At the most vegetative phase of cropping season (i.e. 60 and 90 days after sowing) the MB-C showed a 103 and 46.6% increase over the conventional tillage. In general MB-C and MB-N account for 0.8–7% of total C and total N in the surface layers of arable soils, we observed similar values for the microbial quotient- C (1.16–5.38%) and for the microbial quotient- N (1.72–2.77%) in zero tillage fields. Zero tillage had a greater effect on microbial quotient values under the stubble retained systems and it reflected the seasonal changes and crop growth in the same way as microbial biomass.